Prospecção geofísica em área de ocorrências de manganês supergênico na região de Heliodora, sul de Minas Gerais - Reis, Samuel Siqueira [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This paper discusses the results of combined use of the methods of Electrical Resistivity and Induced Polarization in the geophysical prospection of a supergene manganese mineral occurrence, characterized by manganese and iron oxides with earthy texture, derived from the weathering of spessartite contained in metasediments. From electrical resistivity measurements it was possible to recognize a concentric zone in 2D inversion models, ranging from 73 .m to 380 .m, coinciding with the richer portion in oxides. 2D inversion models for chargeability obtained near the exposed soil profile, helped to determine the entire mineralized zone, characterized by values below 5mV/V. The 3D modeling generated by interpolation of 2D inversion models allowed a morphological analysis of the event, characterized by a wide zone (around 50m) visible on field, but restricted to approximately 10m deep, basically between the horizons B and C of the soil profile. The restriction in depth may be associated with the precipitation of leached metals, in the oxidation-reduction interface provided by the cut in the ground to the road construction, which promotes aeration and soil evapotranspiration. The results reveal the potential of morphological detailing of supergene mineralizations quickly and expeditiously by the combined use of geoelectric methods and data evaluation by 3D modelling

Este trabalho discute os resultados de uso combinado dos métodos da Eletrorresistividade e Polarização Induzida na prospecção geofísica de uma ocorrência mineral de manganês de origem supergênica, caracterizada por óxidos de manganês e ferro com textura terrosa, oriundos do intemperismo de espessartita contida em metassedimentos. A partir das medidas de resistividade elétrica foi possível o reconhecimento de uma zona concêntrica em modelos de inversão 2D, com valores entre 73 .m e 380 .m, coincidente com a porção mais enriquecida em óxidos. Os modelos de inversão 2D para cargabilidade obtidos próximo no perfil de solo exposto, permitiram delimitar toda a extensão mineralizada, caracterizada por valores abaixo de 5mVV. O modelamento 3D gerado por interpolação de modelos de inversão 2D, possibilitou uma análise morfológica da ocorrência, caracterizada por uma extensa faixa (cerca de 50m) visível em campo, mas restrita a cerca de 10m de profundidade, basicamente entre os horizontes B e C do perfil de solo. A restrição em profundidade pode estar associada a precipitação de metais lixiviados, na interface de oxidação-redução proporcionada pelo corte no terreno para construção da estrada, que promove aeração e evapotranspiração do solo. Os resultados relevam o potencial de detalhamento morfológico de mineralizações supergênicas de forma rápida e expedita, pelo uso combinado de métodos geoelétricos e avaliação de dados via modelamento 3D
Keywords: Geofisica; Manganes; Geologia estrutural; Prospecção - Métodos geofísicos; Minas Gerais